PENGARUH KUALITAS PELAYANAN DAN CORPORATE SOCIAL RESPONSIBIITY (CSR) TERHADAP CITRA BMT NU JAWA TIMUR - Huda, Nurul; Maksum, Maksum; Helmi, Moh.; Pratiwi, Angrum (Faculty of Islamic Economics and Business, Sultan Aji Muhammad Idris State Islamic University of Samarinda, 2025)
This study analyzes the influence of Service Quality and Corporate Social Responsibility (CSR) on the formation of the Image of BMT NU East Java as a sharia microfinance institution. Grounded in SERVQUAL theory (Parasuraman et al., 1988), CARTER model for Islamic banking (Othman & Owen, 2001), and Carroll's CSR framework (1991), the research addresses challenges in building positive institutional image for sustainable growth. This quantitative study uses a field approach with incidental sampling techniques on 100 respondents from among Islamic boarding school students who are customers of BMT NU East Java. Data were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regressions, and hypothesis tests through SPSS Statistics 26. The findings reveal that both service quality and corporate social responsibility demonstrate statistically significant positive influences on institutional image formation. Service quality emerges as a critical determinant in shaping customer perceptions, while CSR programs contribute substantially to building trust and credibility. The combined effect of these variables explains the vast majority of institutional image variance, indicating their strategic importance for BMT sustainability and growth. Practically, findings suggest BMT managers should prioritize Islamic finance service training and implement community-focused CSR programs to enhance institutional reputation and competitive positioning in the Islamic microfinance sector.